MicroRNA Profile in Response to Doxorubicin Treatment in Breast Cancer. Issue 9 (September 2015) - Tormo, Eduardo; Pineda, Begoña; Serna, Eva; Guijarro, Alba; Ribas, Gloria; Fores, Jaume; Chirivella, Enrique; Climent, Joan; Lluch, Ana; Eroles, Pilar
ABSTRACT Chemotherapy treatment is the standard in triple negative breast cancers, a cancer subgroup which lacks a specific target. The mechanisms leading to the response, as well as any markers that allow the differentiation between responder and non‐responder groups prior to treatment are unknown. In parallel, miRNAs can act as oncogenes or tumor suppressors and there is evidence of their involvement in promoting resistance to anticancer drugs. Therefore we hypothesized that changes in miRNA expression after doxorubicin treatment may also be relevant in treatment response. Objective: To study miRNAs that are differentially expressed in response to doxorubicin treatment. Methods: One luminal‐A and two triple negative, breast cancer cell lines were exposed to doxorubicin. Microarray analysis was performed to identify the common and differentially modified miRNAs. Genes and pathways that are theoretically regulated by these miRNAs were analyzed. Results: Thirteen miRNAs common to all three lines were modified, in addition to 25 that were specific to triple negative cell lines, and 69 that changed only in the luminal‐A cell line. This altered expression pattern seemed to be more strongly related to the breast cancer subgroup than to the treatment. The analysis of target genes revealed that cancer related pathways were the most affected by these miRNAs, moreover many of them had been previously related to chemotherapy resistance; thus suggesting follow‐up studies. Additionally, through functional assays, we showed that miR‐548c‐3p is implicated in doxorubicin‐treated MCF‐7 cell viability, suggesting a role for this miRNA in resistance. J. Cell. Biochem. 116: 2061–2073, 2015. © 2015 Wiley Periodicals, Inc.